1847: the year of the typographic war. Rafael de Rafael’s specimen and its relevance to the history of Mexican typography - Gravier, Marina Garone (InfoDesign, 2010)
The Nineteenth century was a period of intense political change in Mexico, as well as national independence (1810), there were three foreign interventions in Aztec soil. In this effervescent political context significant technological there were changes in publishing and printing letterpress. This essay presents an unknown type specimen from the Catalan printer Rafael de Rafael, who was the first to print in letterpress with various colors in Mexico. The intent of this text is to review the political context in which these advances in the graphic arts were developed, to analyze the importance of type samples as a source for the history of printing, and describe that document to give it the real space and recognition to the Mexican history of printing in the nineteenth century. [ Download ]